CT of invasive pulmonary aspergillosis (IPA) in cases with hematologic malignancy: Comparison of CT features in the group classified by the severity of neutropenia and underlying disease. Issue 131 (October 2020) - Yanagawa, Noriyo; Sakai, Fumikazu; Doki, Noriko; Sekiya, Noritaka
Abstract: Purpose: To identify differences in the radiological findings of invasive pulmonary aspergillosis (IPA) among patients classified by severity of neutropenia, and differences in underlying disease. Materials and Methods: We retrospectively reviewed computed tomography (CT) scans from the time of the diagnosis of IPA in 83 hematological malignancy patients with probable or proven IPA according to the EORTC-MSG criteria. We evaluated CT findings (radiological pattern, number of lesions, distribution, and presence of low attenuation area [LAA]), and compared the radiological findings of patients classified by degree of neutropenia with two different indicators (neutrophil count at the onset, and c-d -index) and underlying disease. Results: Neutropenia at the onset of IPA was associated with an increased frequency of LAA (p < 0.05), especially in FN (p < 0.01). Cases with a c-d -index of ≧5500 showed an increased incidence of the angio-invasive pattern. In contrast, cases with a c-d -index of 0 showed an increased incidence of the airway-invasive pattern (p < 0.05). The airway-invasive pattern was more frequent in cases with MM, while the angio-invasive pattern was more frequent in cases with AML (p < 0.01). Lower-predominant distribution was more frequent and random distribution was less frequent in cases with AML, random distribution was more frequent and lower-predominant distribution was less frequent in cases with ALL, and upper-predominant distribution was more frequent in cases with MDS (p < 0.05). Conclusions: CT features of IPA vary according to the degree of neutropenia and underlying disease.